2010
DOI: 10.1007/s11154-010-9137-1
|View full text |Cite
|
Sign up to set email alerts
|

SERMs and SERMs with estrogen for postmenopausal osteoporosis

Abstract: Bone loss with aging places postmenopausal women at a higher risk for osteoporosis and its consequences such as fractures, pain, disability, and increased morbidity and mortality. Approximately 200 million patients worldwide are affected. The Third National Health and Nutrition Examination Survey (NHANES III) estimated that up to 18% of US women aged 50 and older have osteoporosis and up to 50% have osteopenia. Greater than 2 million osteoporotic related fractures occurred in the United States with direct heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The SERM ‘ RAL ’ had been proved to prevent postmenopausal osteoporosis . It did not bind to androgen receptors and had no effects on male reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SERM ‘ RAL ’ had been proved to prevent postmenopausal osteoporosis . It did not bind to androgen receptors and had no effects on male reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Raloxifene ( RAL ) is a selective oestrogen receptor modulator (SERM), which exhibits agonistic or antagonistic characters in a cell and tissue. RAL mimics the effects of oestrogens in bone without stimulatory effects in most other tissues . The observations that oestrogens may play a role in bone metabolism of men and that SERMs prevent bone loss in ORX male rats raised the possibility that they may be used in the treatment of elderly men without feminizing side effects .…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen agonists/antagonists, formerly termed selective estrogen receptor modulators (SERMs), which do not stimulate the breast or uterus, can still inhibit bone resorption and prevent bone loss after ovariectomy [ 87 ]. Bone turnover can be decreased by low doses of estrogen, and fracture risk is increased in women with extremely low serum estradiol concentrations [ 88 , 89 ].…”
Section: Sex Hormonesmentioning
confidence: 99%
“…21 Furthermore, several clinical and animal model studies have demonstrated that estrogens function in bone tissue [22][23][24] and have suggested that ER modulators aid in osteoporosis prevention and/or clinical treatment. 25,26 ERs are highly expressed in OPCs, while present at lower levels in osteoclasts. 27 In OPCs, when E2 interacted with the ERα, osteogenic activity is enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogens are vital for maintaining bone mineral density in both mice and humans, 21 while E2 is pro‐osteoblastic, and promotes bone formation 21 . Furthermore, several clinical and animal model studies have demonstrated that estrogens function in bone tissue 22‐24 and have suggested that ER modulators aid in osteoporosis prevention and/or clinical treatment 25,26 . ERs are highly expressed in OPCs, while present at lower levels in osteoclasts 27 .…”
Section: Introductionmentioning
confidence: 99%